Pengaruh Latihan Cone Drill untuk Meningkatkan Kelincahan Siswa Sekolah Dasar Kelas 5 melalui Permainan Olahraga Tradisional Hadang di SDN Banjaran 03 - Dimas Dimas; Budi Budi (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to determine the effect of cone drill training through the traditional Hadang game on improving the agility of fifth-grade students at SDN Banjaran 03. The research used a one-group pretest-posttest design with a quantitative approach. The sample consisted of 11 students selected through purposive sampling. Data were collected using a shuttle run test to measure students' agility levels before and after the intervention, which consisted of Hadang game training for four weeks. Data analysis using a paired sample t-test showed a significant improvement in agility after the intervention, with a significance value (p < 0.05). These findings indicate that the Hadang game, which involves quick movements and frequent direction changes, is effective in enhancing the agility of elementary school students. This study recommends incorporating traditional games as an alternative method in physical education classes to improve students’ physical fitness in a fun and educational manner.